SPEAKING CLUB AS AN INTERACTIVE EXTRACURRICULAR ACTIVITY IN LEARNING ENGLISH FOR PROFESSIONAL PURPOSES AT MEDICAL UNIVERSITIES - Demydovych, Oksana; Holik, Olena (Advanced Education, 2020)
The article aims at evaluating the effectiveness of the Speaking Club in learning English for professional purposes at medical universities. The Speaking Club is presented as an integral part of the foreign language studies that, being a student-driven activity, promotes motivation as well as develops interaction and communication skills of its members. The authors define the concept of the Speaking Club based on the literature review and personal experience, find out effective ways of the Speaking Club organisation as well as describe its structure, roles and responsibilities of the participants. With regard to the management of the Speaking Club sessions, some important principles are defined in the present study. They deal with the interaction and communication style, moral beliefs and values, duration of the sessions and their planning, a topic choice and a format of the event. In the article, the emphasis is made on the main didactic principles applied to the preparation, organisation and hosting of the meetings and include visualisation, accessibility, active participation, systematisation and continuity. The authors carried out a five-year experiment to assess the effectiveness of the Speaking Club in terms of the language proficiency level of the participants and their social activity engagement. The study enrolled 140 students of the National Medical University named after O. O. Bohomolets and included 4 stages that lasted from 2012 to 2017. The research work delivers evidence of overall improvement of the four basic language skills (reading, writing, listening and speaking) and, therefore, a general increase in the English language proficiency level of the Speaking Club participants. According to the general conclusions drawn from the findings obtained before and after the experiment, the Speaking Club proves to be an effective extracurricular activity in learning English for professional purposes at medical universities.